Vanadium nitride and carbon nanofiber composite membrane as an interlayer for extended life cycle lithium-sulphur batteries. Issue 15 (1st August 2021) - Kim, Han-Byeol; Ngo, Duc Tung; Verma, Rakesh; Singhbabu, Yashabanta N.; Kim, Do-young; Le, Hang T.T.; Mali, Sawanta S.; Hong, Chang-Kook; Park, Chan-Jin
Abstract: In this study, carbon nanofibre (CNF) and vanadium-nitride-modified CNF (VNCNF) were fabricated by the electrospinning method, followed by carbonisation. The fabricated VNCNF and CNF were sandwiched between the cathode and separator to be used as interlayers. The lithium-sulphur (Li–S) cell employing the VNCNF interlayer exhibited high initial charge and discharge capacities of 1452 and 1480 mAh g −1, corresponding a coulombic efficiency higher than 100% at a rate of 0.5 C, whereas the cell with the CNF interlayer delivered the initial charge and discharge capacities of 858 and 772 mAh g −1, respectively, corresponding to a coulombic efficiency of 89.97%. Even after 400 cycles, the cell with the VNCNF interlayer retained a remarkable high capacity of 923 mAh g −1, whereas the cell with the CNF interlayer showed only 586 mAh g −1 at a rate of 0.5 C. Furthermore, the cell with the VNCNF interlayer exhibited an excellent rate capability of up to 2 C, which was much higher than those of the cells with CNF and without an interlayer. The better performance of Li–S cell with the VNCNF interlayer is attributed to the strong adsorption ability of VNCNF for polysulphide by suppressing the shuttle effect. In addition, the catalytic effect of VN in CNF accelerated the capturing and utilisation of the dissolved active materials, thereby enhancing the Red-Ox kinetics and capacity. Graphical abstract: Image 1 Highlights: A VNCNF interlayer was proposed as an effective approach to prevent the "shuttle effect" of lithium polysulfide. The VNCNF interlayer was positioned between the battery anode and separator, which aided the suppression of the growth of lithium dendrites. The cycling stability of Li–S batteries was significantly improved due to the VNCNF interlayer. After 400 cycles, the VNCNF interlayer retained a remarkable high capacity of 951 mAh g −1 at a C-rate of 0.5 C.